Scoping Review of Green Innovation Development in Indonesia - Dinata, I Putu Hendy Bimantara; Saragi, Daniel Edgar Hirasma; Firmansyah, Amrie (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2024)
The purpose of this research is to identify the expansion of GI in Indonesia. We use the scoping review method to answer the research objective. This research is divided into three clusters, i.e., the practice of GI in small and medium enterprises, the practice of GI on the listed company in the Indonesia Stock Exchange, and other issues about GI development in Indonesia. GI has been applied in the business sector with broad and varied stakeholders. It positively impacts the firm performance and the company's competitive advantage. This research can have implications for business owners to implement GI immediately.